Variables asociadas a los diagnósticos de enfermería en adultos en Hemódialisis - Asmat Pastor, Mercedes (2021)
The objective of this study was to determine the variables associated with nursing diagnoses in adult hemodialysis therapy. A descriptive and correlational design was used in a sample of 02 patients seen in a renal clinic in Iquitos, to whom a questionnaire of sociodemographic and clinical factors and a checklist of “Nursing Diagnoses of patients on hemodialysis”. Was applied. The findings showed the demographic profile of the hemodialysis adults, almost half were older adults, male, the majority having higher education: Likewise, regarding the underlying disease, six out of ten adults had diabetic nephropathy, five out of ten hypertensive disease. The most frequent actual and potential nursing diagnoses applying the NANDA nomenclatura were the actual diagnoses Excess fluid volumen and Impaired skin integrity and the potential diagnoses Risk of infection, of electrolyte imbalance and of fluid volumen imbalance. Likewise, the diagnoses that were associated with the highest number of nursing diagnoses were Pain and Fatigue (p < 0,01).